Determinants of host susceptibility to murine respiratory syncytial virus (RSV) disease identify a role for the innate immunity scavenger receptor MARCO gene in human infants - High, Monica (2016)
Background: Respiratory syncytial virus (RSV) is the global leading cause of lower respiratory tract infection in infants. Nearly 30% of all infected infants develop severe disease including bronchiolitis, but susceptibility mechanismsremain unclear.Methods: We infected a panel of 30 inbred strains of mice with RSV and measured changes in lung disease parameters 1 and 5 days post-infection and they were used in genome-wide association (GWA) studies to identify quantitative trait loci (QTL) and susceptibility gene candidates.Findings: GWA identified QTLs for RSV disease phenotypes, and the innate immunity scavenger receptor Marco was a candidate susceptibility gene; targeted deletion of Marco worsened murine RSV disease. We characterized a human MARCO promoter SNP that caused loss of gene expression, increased in vitro cellular response to RSV infection, and associated with increased risk of disease severity in two independent populations of children infected with RSV.Interpretation: Translational integration of a genetic animal model and in vitro human studies identified a role for MARCO in human RSV disease severity. Because no RSV vaccines are approved for clinical use, genetic studies have implications for diagnosing individuals who are at risk for severe RSV disease, and disease prevention strategies (e.g. RSV antibodies).